Lessons from East Asia: Comparing Ethiopia and Vietnam's Early-Stage Special Economic Zone Development - Keyi Tang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
This paper by Keyi Tang compares how Ethiopia and Vietnam, two rising stars actively employing industrial policies as catalysts of structural change, have learned from East Asian countries' experiences in developing their own special economic zones (SEZs). A Chinese and a Taiwanese overseas SEZ were the first SEZs developed respectively in Ethiopia and in Vietnam, which provided eye-opening lessons for domestic policymakers on how to better improve the legal and institutional framework, infrastructure, and administrative services needed for SEZ development. Overall, however, one of the biggest obstacles facing Ethiopia and Vietnam in learning from China's experiences is the lack of local autonomy given to SEZs in their own administration.
Keywords: 330